Analysis of a Soil Mixed With Construction And Demolition Waste (CD&W) for use in Road Works (Research, Society and Development, 2022)
The construction industry is responsible for a consumption of 20 to 50% of the existing natural resources on the planet. One way of mitigating the exploitation of natural aggregates extraction deposits and expanding the use of residues is the study of their application in paving. The present article technically analyzed the potential of application of construction and demolition waste (CD&W) in mixtures with sandy-silty soil as a possibility for reuse in the base layer of pavements. The guidelines of the new flexible pavement design method of the Departamento Nacional de Infraestrutura de Transportes (DNIT) propose that the analysis of the materials used in the pavement layers be carried out through the resilience module and permanent deformation. Thus, repeated load triaxial tests were carried out to determine the resilience modulus of soil-crushed and soil-CD&W mixtures in various proportions and later the design of a pavement structure was carried out using the MeDiNa software to verify if mixtures of soil with CD&W aggregates would provide structural base layers with performance comparable to that of conventional crushed rock. From the magnitude of the resilience module of the mixtures and the sizing, the potential of using the soil mixture with local waste in the pavement structure with specific design characteristics and thicknesses was verified. The design using the MeDiNa software proved the possibility of using the soil-CD&W 70-30 mixture in the base layer properly.